Passive Mobilization Analysis To Prevent Decubitus Grade I Ulcuss In Cerebro Vascular Accident Patients - Andri, Florensius; Widoroni, Christianus Eko Purwanto (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The purpose of this study to determine whether passive mobilization can prevent the occurrence of decubitus ulcers in patients with paralysis (CVA). Type of research used in this research is pre experiment. The sample in this study amounted to 16 respondents. Purposive Sampling Sampling Technique. Independent variable is passive mobilization, dependent variable of decubitus ulcers I. The research instrument uses observation sheet of decubitus ulcer wound with Mc Nemar statistic test. There is a sign of ulcer wound and there is no ulcer sign as much as 8 people (50%). Most respondents after passive mobilization there was no signs of ulcers dekubitus that is as many as 14 people (87%). The result of statistical test got significance value is p = 0,031 means reject Ho conclusion there is influence of passive mobilization To Prevent Occurrence of Decubitus Ulcus I Degrees On Patient Paralysis (CVA).